2014
DOI: 10.1186/1471-2393-14-67
|View full text |Cite
|
Sign up to set email alerts
|

Public views of acceptability of perinatal mental health screening and treatment preference: a population based survey

Abstract: BackgroundAt a prevalence rate of 13-25%, mental health problems are among the most common morbidities of the prenatal and postnatal periods. They have been associated with increased risk of preterm birth and low birthweight, child developmental delay, and poor child mental health. However, very few pregnant and postpartum women proactively seek help or engage in treatment and less than 15% receive needed mental healthcare. While system-related barriers limit accessibility and availability of mental health ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
3
21
0
5
Order By: Relevance
“…Study limitations include the low response rate and therefore potential threats to both internal and external validity, yet the 20% response rate is common in studies that use telephone surveys and past Alberta surveys (Kingston et al, 2014). Further, the sample characteristics, in general, reflect the demographic profile of the province, in terms of sociodemographic and socioeconomic characteristics (Statistics Canada, 2012), with the exception that respondents of the Alberta survey were older.…”
Section: Resultsmentioning
confidence: 99%
“…Study limitations include the low response rate and therefore potential threats to both internal and external validity, yet the 20% response rate is common in studies that use telephone surveys and past Alberta surveys (Kingston et al, 2014). Further, the sample characteristics, in general, reflect the demographic profile of the province, in terms of sociodemographic and socioeconomic characteristics (Statistics Canada, 2012), with the exception that respondents of the Alberta survey were older.…”
Section: Resultsmentioning
confidence: 99%
“…The term perinatal mental health problems (PMHPs) refers to the range of psychological distress that healthcare professionals may encounter during this period which may range from depression and anxiety to serious mental health problems (Howard et al, ; Noonan, Doody, et al, ). PMHPs are among the most common morbidities experienced by women with international rates of 13–25% reported (Kingston et al, ). A population survey of the prevalence of antenatal depression in Irish maternity services where the Edinburgh Postnatal Depression Scale (EPDS) was administered found that 15.8% of women scored positive for antenatal depression (Jairaj et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dichas mejoras en la atención psicosocial, solo pueden llevarse a término, como un proceso integrado de detección, evaluación, derivación, tratamiento y seguimiento (Kingston et al, 2014).…”
Section: La Detección Precoz De La Depresión Prenatalunclassified
“…Sobre esta cuestión, Kingston et al (2014) realizaron un estudio con el objetivo de identificar cual era la visión general de la sociedad, con respecto al cuidado de la salud mental y el tratamiento en mujeres embarazadas y posparto, para determinar los factores asociados a esas opiniones. Para llevar a cabo el estudio se realizó una encuesta telefónica asistida por ordenador realizada por el Population Research Laboratory con una muestra aleatoria de adultos en Alberta, Canadá.…”
Section: Barreras Y Facilitadores Relacionados Con El Tratamientounclassified
See 1 more Smart Citation